Education Management in the Quran - Hasnah Hasnah; Fatimah Fatimah; Rifdah Sabrina; Emilza Tri Murni (Ri'ayatu Al-Qur'an: Jurnal Pendidikan Islam, 2024)
Educational management is a structuring of the educational field which is carried out through planning, communicating, motivating, and budgeting, controlling, monitoring and reporting activities systematically to achieve quality educational goals. This study uses a qualitative method with a content analysis approach. In the Quran, there is a word al-mudabbir or event. Event means organizing, managing, leading, planning. This term can be found in QS. Yunus: 3 and 31, QS. Ar-Ra'd: 2. There are five management functions: 1). Planning, QS.al-Hasyr: 18. 2). Organizing QS. Ash-Shaf: 4. 3). Move (actuating), QS. Al-Maidah: 48. 4). Surveillance (controlling), QS. Ali-Imran: 29. 5). Evaluation. QS. Al-A’raf: 168. The Quran further indicates the principles of Islamic education management, including: 1). Sincerity, ihsan and example are found in QS. Al-An'am: 162 and QS. Al-Isra: 7. 2). Honesty, found in QS. Az-Zumar: 33. (3). Trust, found in QS. An-Nisa': 58. 4). Fair, found in QS. Al-Maidah: 8. 5). Responsibility is contained in QS. Al-Baqarah: 286. 6). Dynamic, found in QS. ar-Ra'du: 11. 7). Practically, it is found in QS. Al-Ashr: 1-3. 8). Effective and efficient, found in QS. Al-Kahf: 103-104, al-Isra': 26-27.